A Pilot Study of Mindfulness-Based Exposure Therapy in OEF/OIF Combat Veterans with PTSD: Altered Medial Frontal Cortex and Amygdala Responses in Social–Emotional Processing - King, Anthony P.; Block, Stefanie R.; Sripada, Rebecca K.; Rauch, Sheila A. M.; Porter, Katherine E.; Favorite, Todd K.; Giardino, Nicholas; Liberzon, Israel (Frontiers in Psychiatry, 2016)
Combat-related PTSD is common among returning veterans, and is a serious and debilitating disorder. While highly effective treatments involving trauma exposure exist, difficulties with engagement and early drop may lead to sub-optimal outcomes. Mindfulness training may provide a method for increasing emotional regulation skills that may improve engagement in trauma-focused therapy. Here we examine potential neural correlates of mindfulness training and in vivo exposure (non-trauma focused) using a novel group therapy (Mindfulness-based Exposure Therapy) in Afghanistan (OEF) or Iraq (OIF) combat veterans with PTSD. OEF/OIF combat veterans with PTSD (N=23) were treated with MBET (N = 14) or a comparison group therapy (Present-centered group therapy [PCGT], N = 9). PTSD symptoms were assessed at pre- and post-therapy with Clinician Administered PTSD scale (CAPS). Functional neuroimaging (3 Tesla fMRI) before and after therapy examined responses to emotional faces (angry, fearful, and neutral faces). Patients treated with MBET had reduced PTSD symptoms (effect size d = .92) but effect was not significantly different from PCGT (d = .43). Improvement in PTSD symptoms from Pre- to Post treatment in both treatment groups was correlated with increased activity in rostral ACC, dorsal medial PFC, and left amygdala. The MBET group showed greater increases in amygdala and fusiform gyrus responses to Angry faces, as well as increased response in left medial PFC to Fearful faces. These preliminary findings provide intriguing evidence that MBET group therapy for PTSD may lead to changes in neural processing of social-emotional threat related to symptom reduction.